Consider this quadratic equation. x2 + 1 = 2x – 3 Which expression correctly sets up the quadratic formula?
Question
x2 + 1 = 2x – 3
Which expression correctly sets up the quadratic formula?
2 Answer

1. User Answers chinaknos12
Answer:A
Stepbystep explanation:

2. User Answers nuhulawal20
The equation that best set up the quadratic formula is [tex]x = \frac{ (2) + \sqrt{(2)^24(1)(4)} }{2(1)}[/tex].
Hence, option A is the correct answer.
What is a Quadratic Equation?
Quadratic equation is simply an algebraic expression of the second degree in x. Quadratic equation in its standard form is;
ax² + bx + c = 0
Where x is the unknown
Using the quadratic formula
x = (b±√(b²  4ac)) / (2a)
Given that;
x² + 1 = 2x – 3
First we rearrange the the equation.
x² + 1 = 2x  3
x²  2x + 1 + 3 = 0
x²  2x + 4 = 0
Hence;
 a = 1
 b = 2
 c = 4
Next we input this values into the quadratic formula
x = (b±√(b²  4ac)) / (2a)
x = ((2)±√((2)²  4(1)(4))) / (2(1))
[tex]x = \frac{ (2) + \sqrt{(2)^24(1)(4)} }{2(1)}[/tex]
The equation that best set up the quadratic formula is [tex]x = \frac{ (2) + \sqrt{(2)^24(1)(4)} }{2(1)}[/tex].
Hence, option A is the correct answer.
Learn more about quadratic equations here: brainly.com/question/1863222
#SPJ5